Laser machining of glass fibre reinforced plastics (GFRP) - Kolandaisamy, Robert Milkey (2014)
Glass fibre reinforced plastics (GFRP) composite materials are in increasingly high demand, particularly in marine industries for reduced weight. This is due to their superior structural characteristics (in fatigue and static conditions) as well as light weight. Anisotropic and heterogeneous features of these materials, however, have posed serious challenges in machining of GFRP. Hence, a new machining technology needs to be investigated. Laser is a non-contact process which is identified as being satisfactory for this research project. A major quality challenge in terms of the laser cutting quality of these materials includes dimensional accuracy. Various laser parameters and cutting techniques are investigated in this study to minimise these defects. In order to improve the cutting quality and dimensional accuracy, design parameters and responses were correlated, modelled, analysed, optimized and experimentally validated to meet the requirements of marine engineering sponsored industry. The objective of this research work is to study the different aspects of GFRP composite cutting using CO2 laser and to establish the relationship between the kerf width, taper and roundness with the process parameters like laser power, cutting speed, gas pressure, frequency and duty cycle. The experimental plans were conducted according to the design of experiment (DOE) to accommodate a full range of experimental analysis. Identification of the important parameter effects presented using analysis of variance (ANOVA) technique combined with graphical representation provides a clearer picture of the whole laser profiling phenomenon. The results show that, the interaction between lower level laser power (2600 Watt), higher level cutting speed (1200 mm/min), higher level gas pressure (8 Bar), medium level frequency (1825 Hz) and medium level duty cycle (96 %) gives better cutting performance towards three responses. Finally, the predictive mathematical model that was established to predict the responses were also validated and are found to be promising in resolving the cut quality issues of industrial GFRP laminates with the error value 16.12 % for kerf width, 18.60 % for taper and 16.28 % for roundness. It was demonstrated that, the response surface methodology (RSM) has played a valuable role to identify the interaction factors of design parameters in attaining industrial desired cut quality response.